65.1k views
0 votes
Solve the equation. 2x + 4x + 6x - 2(x + 3) = 34

What equals x?

User Eloyesp
by
5.3k points

1 Answer

1 vote

Answer:


\boxed { x = 4}

Explanation:

Solve for the value of
x:


2x + 4x + 6x - 2(x + 3) = 34

-Combine like terms:


2x + 4x + 6x - 2(x + 3) = 34


12x - 2(x + 3) = 34

-Use Distributive Property:


12x - 2(x + 3) = 34


12x - 2x - 6 = 34

-Combine like terms:


12x - 2x - 6 = 34


10x - 6 = 34

-Add
6 to both sides:


10x - 6 + 6 = 34 + 6


10x = 40

Divide both sides by
10:


(10x)/(10) = (40)/(10)


\boxed { x = 4}

Therefore, the value of
x is
4.

User Stewie
by
4.6k points